Hubungan Karakter Tanggung Jawab, Disiplin, dan Kerja Keras dengan Capaian Akademik Mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Medan - Saragih, Kevin Pardomuan; Afifah, Naila Aulia; Sitohang, Putri Estania; Salsabila, Afifah; Setianta, Maykel Putra; Salsabila, Nur Afifah (CV. Eracita Grup, 2026)
This study aims to determine the relationship between the characteristics of responsibility, discipline, and hard work with the academic achievement of students at the Faculty of Education, State University of Medan. This study uses a descriptive quantitative approach with a correlational design. The research subjects were 25 students of the 2023 batch from several study programs at the Faculty of Education selected using a purposive sampling technique. Data collection was conducted through an online questionnaire based on Google Forms that measured students' dominant character traits and academic indicators, such as Grade Point Average (GPA), academic engagement, organizational activity, and learning behavior. Data were analyzed using descriptive statistical techniques with the help of the Jamovi application. The results showed that most students had positive dominant character traits, namely responsibility, discipline, and hard work. The average student GPA was 3.60, which is classified as good. The research findings indicate a positive relationship between dominant character traits and student academic achievement, where students with higher levels of responsibility, discipline, and hard work tend to have better academic achievement. This study emphasizes the importance of character development as an internal factor that supports student academic success in higher education.